1994
DOI: 10.1017/s0016756800012838
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy, structure and geochronology of the Las Cañadas caldera (Tenerife, Canary Islands)

Abstract: After a long period of subaerial fissure-fed extrusions of basaltic magmas (∼ 12 to > 3 Ma) volcanic activity was then concentrated in the central part of Tenerife. Phonolitic magma chambers formed and a central volcanic complex was constructed (the Las Canadas edifice). The formation of a large depression (the Las Canadas caldera) truncated the top of the edifice. The active twin strato-cones Teide—Pico Viejo are sited in this depression. The history of the Las Canadas caldera and edifice are established f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
268
1
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 260 publications
(282 citation statements)
references
References 26 publications
5
268
1
8
Order By: Relevance
“…The abundance of high-density bodies in that part of the caldera depression is in perfect agreement with ring fault formation and initiation of the vertical collapse there. The combination of results from these potential field investigations (gravity, magnetotellury and magnetics) provides irrefutable evidence for a vertical collapse origin of the LCC, which is also supported by the abundance of voluminous products of phonolitic explosive (caldera-forming) volcanism on the island (Martí et al, 1994;Edgar et al, 2007;Pittari et al, 2008) It has been suggested by various authors that the head of the Icod valley is buried beneath eruptive products of the PV-PT complex (Martí et al, 1997;Martí et al, 1998;Ablay and Hürlimann, 2000). The horseshoe-shaped alignment of shallow rooted high density bodies to the north of the complex gives the impression of a structural barrier between the complex and the topographic expression of the Icod valley, coinciding with a significant break in slope (Fig.…”
Section: B the Core Of The Cvcmentioning
confidence: 93%
See 3 more Smart Citations
“…The abundance of high-density bodies in that part of the caldera depression is in perfect agreement with ring fault formation and initiation of the vertical collapse there. The combination of results from these potential field investigations (gravity, magnetotellury and magnetics) provides irrefutable evidence for a vertical collapse origin of the LCC, which is also supported by the abundance of voluminous products of phonolitic explosive (caldera-forming) volcanism on the island (Martí et al, 1994;Edgar et al, 2007;Pittari et al, 2008) It has been suggested by various authors that the head of the Icod valley is buried beneath eruptive products of the PV-PT complex (Martí et al, 1997;Martí et al, 1998;Ablay and Hürlimann, 2000). The horseshoe-shaped alignment of shallow rooted high density bodies to the north of the complex gives the impression of a structural barrier between the complex and the topographic expression of the Icod valley, coinciding with a significant break in slope (Fig.…”
Section: B the Core Of The Cvcmentioning
confidence: 93%
“…The geological and tectonic evolution of the triangular island of Tenerife and the CVC was described in recent papers (Martí et al, 1994;Martí et al, 1998;Araña et al, 2000) and we therefore only provide a short summary. The Canary Islands form a volcanic archipelago with a long-standing history of volcanic activity that began more than 40 million years ago (Araña and Ortíz, 1991).…”
Section: Geological Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Son numerosos los estudios dedicados al Edificio Cañadas, que incluyen abundantes dataciones radiométricas (Ancochea et al, 1990(Ancochea et al, , 1999Mitjavila y Villa, 1993;Martí et al, 1994). Sin embargo, los trabajos publicados sobre el Teide y el sistema de rifts, la actividad eruptiva más reciente de la isla, son escasos y apenas incluyen dataciones absolutas, especialmente en el caso del Teide.…”
Section: Introductionunclassified